MENELAAH AL-QURAN DAN HADIST FILANTROPI ISLAM “Perbandingan Tafsir Ibnu Kastir dan Tafsir Fi Zhilalil Qur’an” - Mufida, Maugfira Helni (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2022)
Philanthropy in Islam leads to social treatment of the community, which has an important role in building, upholding justice and providing space for people who need resources that have not been met in fulfilling their needs. The practice of philanthropy in Islam through zakat, infaq, alms, and waqf (ZISWAF). In addition, Islamic philanthropy has made an important contribution to the economic empowerment of the community at large in the midst of existing social inequalities. Emphasizes human values ​​and carries moral values, with the principle of equalizing human degrees with other humans. The method that the author uses in this research is qualitative, by collecting various data in good form from written words that have been observed, and not from numbers. This study focuses on the views of some scholars regarding philanthropy that provide an understanding of the importance of philanthropy which is recommended in Islam by embedding the Al-Quran and the Hadith of the Prophet as a reference in interpretation. Not only fixated on the interpretation of the opinion of one scholar, comparing opinions between scholars is also important. With regard to the above explanation, the purpose of this study is to find out the Hadith, Verses and Tafsir of travelers related to ziswaf.